Percutaneous release of trigger finger and its functional outcome - Maheshwari, Sulabh; Mishra, Aditya K.; Saxena, Raunaq; Kaleem, Bilal; Badoni , Navneet (International Journal of Research in Orthopaedics, 2024)
Background: An overview of percutaneous release for trigger finger and its functional outcomes. Methods: The present prospective controlled analytical study was conducted after taking approval from center human ethical committee. A written and informed consent was obtained. There were 50 patients who reported to outpatient department (OPD) with symptoms suggestive of trigger thumb/ finger, were subjected to the study. Results: Most of the patients belonged to the age group of 41-50 years. Majority of patients were females (56%) and males were (44%). Most of the patients had the right 1st digit involved (32%), followed by left 1st and right 3rd digit (18% each). Before the release of affected digit, 56% were grade 3, 26% were grade 4 and only 18% were grade 1. Complete resolution immediately after the procedure was seen in 82% cases. Pre procedure, mean VAS of 8.4 reduced to mean VAS of 6.2 immediate post procedure. At 48 hours post procedure, mean VAS of 3.06 and mean VAS of 1.12 was seen at 1-month post procedure period. At 3 months post procedure, mean VAS of 0.42. 94% cases had no complications. Conclusions: Percutaneous release of trigger finger is a safe and effective procedure associated with favorable functional outcomes. It provides an alternative treatment option for patients who have failed conservative management or prefer a minimally invasive approach.